(untitled) (Research, Society and Development, 2020)
Biological control, with the use of entomopathogenic fungi, has been one of the promising alternatives in the control of fruit flies. This study aimed to evaluate the pathogenicity of entomopathogenic fungi of the species Metarhizium anisopliae (Metsch.) Sorok. and Beauveria bassiana (Bals.) in 2nd and 3rd instar larvae, pupae and adults of the fruit fly Ceratitis capitata Wiedemann (Diptera: Tephritidae). The experiment was conducted at the Invertebrate Zoology and Phytopathology Laboratories at the Center for Agricultural Sciences, Federal University of Paraíba, in the municipality of Areia - PB. In this study, two isolates, Metarhizium anisopliae IDCB425 and Beauveria bassiana IDCB66, were used in different concentrations. It was found that the potential for infection of both isolates is greater in larvae of 2nd and 3rd instars and adults of C. capitata, than in pupae. The mortality rate of C. capitata increases as the suspensions become more concentrated. The IDCB66 isolate from B. bassiana is more efficient to C. capitata than the IDCB425 isolate from M. anisopliae.